2022
DOI: 10.1021/acs.jcim.2c00511
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Simulations Elucidate the Impact of U2AF2 Cancer-Associated Mutations on Pre-mRNA Recognition

Abstract: The U2AF2 splicing factor, made of two tandem RNA recognition motifs (RRMs) joined by a flexible linker, selects the intronic polypyrimidine sequence of premature mRNA, thus ensuring splicing fidelity. Increasing evidence links mutations of key splicing factors, including U2AF2, to a variety of cancers. Nevertheless, the impact of U2AF2 cancer-associated mutations on polypyrimidine recognition remains unclear. Here, we combined extensive (18 μs-long) all-atom molecular dynamics simulations and dynamical networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…At the same time though, we wish to stress that the FUS-RNA system is challenging in many aspects and that the poor performance of the force field reported here cannot be simply generalized for a broad range of RNA–protein systems. To be more optimistic, for many less challenging RNA–protein complexes, the OL3+ff14SB­(ff12SB) combination with SPC/E or similar TIP3P water model is sufficiently accurate without any such modifications. ,,, In the Supporting Information, we provide a recommended best-practice protocol for simulating RNA–protein complexes based on our up-to-date experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time though, we wish to stress that the FUS-RNA system is challenging in many aspects and that the poor performance of the force field reported here cannot be simply generalized for a broad range of RNA–protein systems. To be more optimistic, for many less challenging RNA–protein complexes, the OL3+ff14SB­(ff12SB) combination with SPC/E or similar TIP3P water model is sufficiently accurate without any such modifications. ,,, In the Supporting Information, we provide a recommended best-practice protocol for simulating RNA–protein complexes based on our up-to-date experience.…”
Section: Resultsmentioning
confidence: 99%
“…To be more optimistic, for many less challenging RNA−protein complexes, the OL3+ff14SB-(ff12SB) combination with SPC/E or similar TIP3P water model is sufficiently accurate without any such modifications. 35,55,68,69 In the Supporting Information, we provide a recommended best-practice protocol for simulating RNA− protein complexes based on our up-to-date experience.…”
Section: Thementioning
confidence: 99%
“…Indeed, a high cation density exists between two loops at the RRM1−RRM2 interface close to the binding region of U/C6, a second cation density is placed at the RRM1 α-helix nearby the U8 backbone, and another is placed between the U8 aromatic ring and linker loop. Remarkably, two cancer-associated mutations (i.e., N196K and D231N) 14 affecting the overall charge of U2AF2 surface lie in the vicinity of these cation density hotspots. Interestingly, in the polyC system, these density peaks are complemented by two additional Na + density hotspots placed nearby C3 and C4 (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…In our calculations, we have not considered the entropic contribution of the free energy as it was reported that this term does not substantially improve the quality of the results . Moreover, a per-residue decomposition analysis was done following a procedure applied in previous publications . In the Results section, we only qualitatively discuss the results of the MM-PBSA calculation …”
Section: Methodsmentioning
confidence: 99%
“…Rozza et al. identity cross-communication pathways in mutational hotspots and a dynamical interplay between U2AF2 splicing factor recognition domains and premature mRNA . Finally, Bartocci et al simulate the dynamical “walk” of sulfonated calix-[4]-arenes on cytochrome c and find an allosteric reinforcement of residue interactions with the quasi-harmonic multibasin method …”
mentioning
confidence: 99%